Analysis of Learning in Implementing Digital Technology Based on Power Point at SD Muhammadiyah Karangkajen IV - Lovandri Dwanda Putra; Cintia Maharani Putri; Razita Masturah; Bagas Dwi Setiawan (Indonesian Journal of Education and Mathematical Science, 2023)
Technology is the result of knowledge development in the field of education. Education is an essential part of improving life and nation-building. Effective education involves actively engaging students and developing their skills while learning in the classroom. Our research aims to analyze learning through the implementation of digital technology in the fourth-grade class at SD Muhammadiyah Karangkajen IV. We used a qualitative descriptive research method, utulizing classroom action research techniques,and conducted interviews with the fourth-grade homeroom teacher. Based on the research conducted, students applied learning theories using visual and audiovisual media during the teaching and learning process. As a result, 75% of the total number of fourth-grade students understood the subject matter and utilized the Power Point media optimally. The implementation of digital technology in SD Muhammadiyah Karangkajen IV can enhance students’ quality and learning development, leading to increased focus, concentration, and motivation due to the engaging learning content presented through Power Point.